Analysis of Financial Report Preparation Based on ISAK 35: A Case Study of Sirajul Huda Islamic Boarding School, Tigabinanga District, Karo Regency - Azizah, Nur; Jannah, Nurul; Syafina, Laylan (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the implementation of ISAK 35 standards in the financial reporting of Pondok Pesantren Sirajul Huda located in Tigabinanga District, Karo Regency. A qualitative descriptive approach was used to identify the challenges and practical solutions faced by the pesantren in adopting the standard. The results indicate that the financial recording system is still manual and does not comply with the standards, mainly due to the limited understanding of accounting standards among the management and the lack of regular training. Recommendations include improving accounting literacy through training, implementing application-based recording systems, and preparing structured financial statements in accordance with ISAK 35. It is expected that the findings of this study can serve as a reference for other Islamic boarding schools in enhancing the quality of financial reporting and promoting transparency in sharia-based financial management.